Assessing the Heamatology of Uda Rams Fed Graded Levels of Processed Cassava (Manihot esculentus L.) Peels - , M. M. Mika’ilu; , A. A. Kwaido; , S. A. Maigandi; , I. M. Ribah; , K. M. Aljameel; , A. K. Muhammad (Archives of Current Research International, 2021)
The experiment was carried out at Kebbi State University of Science and Technology, Aliero using thirty two (32) yearlings Uda Rams in two feeding trials ran concurrently. Sixteen (16) rams were used in each experiment with four treatments replicated four times in a completely randomized factorial design (2 × 4). The animal represents the replicates while the processing method (drying and ensiling) and the level of inclusion represents the treatments respectively. The level of inclusion are 0, 10, 20 and 30% dried cassava peels (DCP) and ensiled cassava peels (ECP) respectively. Data were collected in each trial on hematological characteristics. Data generated was subjected to analysis of variance and least significant difference (LSD) was used to separate the means. Hematological values of rams fed DCP were within the normal range while those fed ECP were below the normal range. The results shows significant difference (P<0.05) between dried and ensiled method of processing in terms of haemoglobin, MCH, WBC and MCV. Rams fed dried cassava peels had lower haemoglobin and PCV compared to normal range. It was concluded that there was no significant difference between rams fed dried cassava peels and those fed ensiled cassava peels at 30% level of inclusion.